Efficient electrocatalysts refined from metal-dimer-anchored PC6 monolayers for NO reduction to ammonia - Wu, Jie; Yu, Yang-Xin (International journal of hydrogen energy, 2023)
An electrochemical nitric oxide (NO) reduction reaction (NORR) can not only eliminate the harmful pollutant but also offer a green approach for ammonia synthesis under mild conditions. However, the activities and Faradaic efficiencies of present electrocatalysts are still not suitable for commercial applications and the mechanism has been rarely studied in detail. Here, by means of first-principles calculations and microkinetic modeling, the potentials of a series of metal-dimer anchored on the PC6 monolayer (M2/PC6 BAC) as efficient NORR electrocatalysts were examined. Thirteen possible pathways are taken into consideration for the NORR process and a comprehensive reaction network is first constructed. Consequently, the Cr2/PC6, Mn2/PC6, Fe2/PC6 and Re2/PC6 BACs are screened out as promising candidates for NORR catalysis. Particularly, the Fe2/PC6BAC exhibits the best performance among the studied BACs and its NORR rate constant (2.73 × 107 s−1) at 298.15 K is several orders of magnitude larger than those of the other BACs. It can be known from the electronic calculations that the nature of the interaction between NO and the metal-dimer is ascribed to the donation-backdonation mechanism. This work not only provides eligible BACs for NH3 synthesis but also offers an atomic understanding on the NORR process. [Display omitted] •Eight metal-dimer-anchored PC6 monolayers were screened out as efficient NORR catalysts.•The Cr2/PC6, Mn2/PC6, Fe2/PC6 and Re2/PC6 BACs possess excellent high selectivity.•The Fe2/PC6 BAC exhibits the best catalytic performance for NORR.•The AIMD simulations showed that the Fe2/PC6 BAC exhibits good stability.